Effects of different forms of yeast Saccharomyces cerevisiae on growth performance, intestinal development, and systemic immunity in early-weaned piglets. Issue 1 (December 2015) - Jiang, Zongyong; Wei, Shaoyong; Wang, Zhilin; Zhu, Cui; Hu, Shenglan; Zheng, Chuntian; Chen, Zhuang; Hu, Youjun; Wang, Li; Ma, Xianyong; Yang, Xuefen
Abstract The present study was conducted to determine effects of different forms of yeast (Saccharomyces cerevisiae, strain Y200007) on the growth performance, intestinal development, and systemic immunity in early-weaned piglets. A total of 96 piglets (14-d old, initial average body weight of 4.5 kg) were assigned to 4 dietary treatments: (1) basal diet without yeast (Control); (2) basal diet supplemented with 3.00 g/kg live yeast (LY); (3) basal diet supplemented with 2.66 g/kg heat-killed whole yeast (HKY); and (4) basal diet supplemented with 3.00 g/kg superfine yeast powders (SFY). Diets and water were providedad libitum to the piglets during 3-week experiment. Growth performance of piglets was measured weekly. Samples of blood and small intestine were collected at days 7 and 21 of experiment. Dietary supplementation with LY and SFY improved G:F of piglets at days 1-21 of the experiment (P  < 0.05) compared to Control group. Serum concentrations of growth hormone (GH), triiodothyronine (T3 ), tetraiodothyronine (T4 ), and insulin growth factor 1 (IGF-1) in piglets at day 21 of the experiment were higher when fed diets supplemented with LY and SFY than those in Control group (P  < 0.05). Compared to Control group, contents of serum urea nitrogen of piglets were reduced by the 3 yeast-supplemented diets (P  < 0.05). Diets supplemented with LY increased villus height and villus-to-crypt ratio in duodenum and jejunum of piglets (P  < 0.05) compared to other two groups at day 7 of the experiment. Feeding diets supplemented with LY and SFY increased (P  < 0.05) serum concentrations of IgA, IL-2, and IL-6 levels in piglets compared to Control. The CD4+ /CD8+ ratio and proliferation of T-lymphocytes in piglets fed diets supplemented with LY were increased compared to that of Control group at day 7 of the experiment (P  < 0.05). In conclusion, dietary supplementation with both LY and SFY enhanced feed conversion, small intestinal development, and systemic immunity in early-weaned piglets, with better improvement in feed conversion by dietary supplementation with LY, while dietary supplementation with SFY was more effective in increasing systemic immune functions in early-weaned piglets.